2012
DOI: 10.1177/0269215512444633
|View full text |Cite
|
Sign up to set email alerts
|

Study of the therapeutic effects of a hippotherapy simulator in children with cerebral palsy: a stratified single-blind randomized controlled trial

Abstract: Hippotherapy with a simulator can improve sitting balance in cerebral palsy children who have higher levels of disability. However, this did not lead to a change in the overall function of these children (Gross Motor Function Classification System level V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 30 publications
(43 reference statements)
3
66
1
4
Order By: Relevance
“…However, a review of the literature found that this scale had been used previously in studies of the effects of hippotherapy among CP patients. Hamill et al applied it in assessing the postures of children with cerebral palsy undergoing hippotherapy over 10 weeks [10], while Herrero et al used the SAS to evaluate the therapeutic effect of a hippotherapy simulator among patients with cerebral palsy [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a review of the literature found that this scale had been used previously in studies of the effects of hippotherapy among CP patients. Hamill et al applied it in assessing the postures of children with cerebral palsy undergoing hippotherapy over 10 weeks [10], while Herrero et al used the SAS to evaluate the therapeutic effect of a hippotherapy simulator among patients with cerebral palsy [11].…”
Section: Discussionmentioning
confidence: 99%
“…na pod sta wie m.in. ska li SAS oce nia li te ra peutycz ny wpływ sy mu la to ra hi po te ra pii w gru pie chorych z mó zgo wym po ra że niem [11].…”
Section: Dys Ku Sjaunclassified
“…Therefore, many studies have explored horse riding equipment that offers horse-like movements, which is used to treat various diseases [17][18][19][20][21][22][23]. But so far, a study on change of static balance ability by targeting patient with stroke is not sufficient in reality.…”
Section: Introductionmentioning
confidence: 99%
“…El grupo control recibió un programa de ejercicios, mientras que el grupo estudio recibió el tratamiento de hipoterapia, además del mismo programa de ejercicios que el grupo A. Al finalizar el programa de hipoterapia observaron una mejoría significativa en todas las variables de medición de los dos grupos, pero con una mayor mejoría en el grupo que había realizado las sesiones de hipoterapia. Herrero et al (2012) investigaron si la hipoterapia (cuando se aplica por un simulador) mejora el control postural y el equilibrio en los niños con parálisis cerebral. Para ello seleccionaron treinta y ocho niños de entre 4 y 18 años de edad con parálisis cerebral.…”
Section: Resultsunclassified